Active control of dual electromagnetically induced transparency in terahertz graphene-metal hybrid metasurfaces - Li, Quan; Su, Hao; Zhu, Jun; Wang, Shuang (Frontiers in Materials, 2022)
Active control of electromagnetically induced transparency (EIT) using metasurfaces has attracted growing interests in recent years, especially the ones that have multiple EIT windows. Here, we give out a metallic metasurface design that can achieve dual EIT (D-EIT) in the terahertz (THz) regime, and propose a strategy to individually and simultaneously control the two windows by integrating graphene structures into the design. The near-field simulations indicate that the physical mechanism lies in the composite effect of conductive graphene. The theoretical analysis reveals that the active modulation is attributed to the changes in the damping rates of the dark modes and the coupling coefficients between bright mode and dark modes. The proposed graphene-metal hybrid metasurfaces provide a way for designing compact dual-band slow-light and modulation devices, which may find potential applications in dual-frequency-channel THz wireless communications.